Clarify your complex basic!

Algebra Level 2

x 2 + 18 x + 90 = 0 \large x^2 + 18x + 90 = 0

Find the value(s) of x x satisfying the equation above.

If the answers are of the form a i b -ai - b and a i b ai - b , with positive a a , submit your answer as a + b a+b .

Clarification : i = 1 i=\sqrt{-1} .

Bonus : Try to solve it without using the quadratic formula .


The answer is 12.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Hung Woei Neoh
May 5, 2016

Use the quadratic formula to solve this equation

x 2 + 18 x + 90 = 0 x = 18 ± 1 8 2 4 ( 1 ) ( 90 ) 2 ( 1 ) = 18 ± 324 360 2 = 18 ± 36 2 = 9 ± 9 = 9 ± 3 i x^2+18x+90=0\\ x=\dfrac{-18 \pm \sqrt{18^2 - 4(1)(90)}}{2(1)}\\ =\dfrac{-18 \pm \sqrt{324-360}}{2}\\ =\dfrac{-18 \pm \sqrt{-36}}{2}\\ =-9 \pm \sqrt{-9}\\ =-9 \pm 3i

Therefore, x = 3 i 9 , x = 3 i 9 x=3i - 9, \; x=-3i-9

a = 3 , b = 9 a=3,\; b=9 and a + b = 3 + 9 = 12 a+b = 3+9 = \boxed{12}

Bonus:

x 2 + 18 x + 90 = 0 x 2 + 18 x + 81 = 9 ( x + 9 ) 2 = 9 x + 9 = ± 9 x + 9 = ± 3 i x = ± 3 i 9 x^2+18x+90=0\\ x^2+18x+81=-9\\ (x+9)^2 = -9\\ x+9 = \pm \sqrt{-9}\\ x+9 = \pm 3i\\ x= \pm 3i - 9

Therefore, x = 3 i 9 , x = 3 i 9 x=3i - 9, \; x=-3i-9

a = 3 , b = 9 a=3,\; b=9 and a + b = 3 + 9 = 12 a+b = 3+9 = \boxed{12}

Yes that is another way :)

Ashish Menon - 5 years, 1 month ago

Log in to reply

You told to try without that formula ..so I did it the other way

Abhiram Rao - 5 years, 1 month ago
Ashish Menon
May 5, 2016

x 2 + 18 x + 90 = 0 x 2 + 18 x + 81 + 9 = 0 ( x + 9 ) 2 9 i 2 = 0 ( x + 9 ) 2 ( 3 i ) 2 = 0 ( x + 9 + 3 i ) ( x + 9 3 i ) = 0 x = ( 3 i 9 ) ( or ) ( 3 i 9 ) a + b = 3 + 9 = 12 \begin{aligned} x^2 + 18x + 90 & = 0\\ x^2 + 18x + 81 + 9 & = 0\\ {\left(x + 9\right)}^2 - 9i^2 & = 0\\ {\left(x + 9\right)}^2 - {\left(3i\right)}^2 & = 0\\ \left(x + 9 + 3i\right)\left(x + 9 - 3i\right) & = 0\\ x & = \left(-3i - 9\right) (\text{or}) \left(3i - 9\right)\\ \therefore a + b & = 3 + 9\\ & = \boxed{12} \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...